Co-morbid mental health conditions in people with epilepsy and association with quality of life in low- and middle-income countries: a systematic review and meta-analysis - Tsigebrhan, R; Derese, A; Kariuki, SM; Fekadu, A; Medhin, G; Newton, CR; Prince, MJ; Hanlon, C (BioMed Central, 2023)
Background Comorbid mental health conditions are common in people with epilepsy and have a significant negative impact on important epilepsy outcomes, although the evidence is mostly from high-income countries. This systematic review aimed to synthesise evidence on the association between comorbid mental health conditions and quality of life and functioning among people with epilepsy living in low- and middle income countries (LMICs).